Food Intake, Infectious Disease, and Environmental Sanitation in Toddlers Aged 6-24 Months in Cibatu Health Center, Garut - Yusigania, Dinna; Dewanti, Linda; Suryawan, Ahmad (Universitas Airlangga, 2024)
Highlights: This study found a significant relationship between food intake, environmental sanitation, and the incidence of infectious diseases in toddlers with stunting. Each variable (food intake, infectious diseases, and environmental sanitation) demonstrated a significant association with the stunting category, indicating their importance in addressing stunting in the target population. Abstract Introduction: Indonesia is a developing nation with complex issues, particularly regarding nutrition. Stunting is a nutrient deficiency that persists over time as a result of being fed food that is not sufficient to meet nutritional requirements. This study aimed to analyze the relationship between food intake, illness, and environmental sanitation in the stunting category in toddlers aged 6-24 months at Cibatu Health Center, Garut, in 2022. Methods: This was a correlational analytical study with a cross-sectional design. The population in this study was all toddlers with stunting (aged 6-24 months) at Cibatu Health Center, Garut, with a total sample of 99 people. The sampling technique used was total sampling. The analysis techniques used were univariate, bivariate, and multiple correlation analyses with a significance level of p < 0.05. Results: There was a significant relationship between food intake, environmental sanitation, and the incidence of infectious diseases in the stunting category, where the p-value (each) was <0.05. Food intake (X1), infectious diseases (X2), and environmental sanitation (X3) had a significant relationship with the stunting category (Y), where the p-value was < 0.05. Conclusion: Food intake, environmental sanitation, and the incidence of infectious diseases had a significant relationship with the stunting category at Cibatu Health Center, Garut.